Organizational Effectiveness with Mckinsey 7s Model Approach on Public Health Center in Madura, Indonesia - Sukartini, Tintin; Masfi, Achmad; Hidayat, A. Aziz Alimul; Nursalam, Nursalam (International Journal of Psychosocial Rehabilitation, 2020)
Public Health Centre (Puskesmas) has many challenges in providing health services, it was caused by many factors. This study aimed to analyze organizational effectiveness with McKinsey 7s model approach on puskesmas performance in Sampang Madura district. An explorative survey design with 226 nurses with stratified random sampling as a sample. Data were analyzed by using SEM (Structural Equation Modelling) PLS (Partial Least Square). Leadership, salary, service, policy and human research are measured by McKinsey 7S Framework Model development. The outer model result is based on the result of validity and reliability of indicator, from the research showed that the indicators below 0.6 on the loading factor table are variable of service, sub-variable system and policy. After the factor loading value <0.6 is removed, the value of AVE and composite reliability is increasing, so all value are > 0.5 for AVE and > 0.7 for composite reliability. The result of the inner model showed that T-Test value > 1.96, indicating that all variables of organizational effectiveness with the McKinsey 7S Framework Model approach significantly to Puskesmas Performance with T-test value > 1.96. MC Kinsey 7S Framework Organizational Effectivity can be implemented as a rule and also joint commitment between Health and Puskesmas easy to monitor and evaluated ,